2021
DOI: 10.3390/ijerph182211743
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Health Literacy among Outpatient Caregivers during the COVID-19 Pandemic

Abstract: Health literacy became an important competence during the COVID-19 pandemic. Despite outpatient caregivers being a particularly vulnerable occupational group, their health literacy has hardly been examined yet, especially during the pandemic. Hence, this study aimed to explore this field and provide first empirical insights. Data were collected based on a cross-sectional online survey among 155 outpatient caregivers. In particular, health literacy (HLS-EU-Q16), diet and physical activity, pandemic-related worr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 132 publications
1
7
0
1
Order By: Relevance
“…Furthermore, a study of German semi-residential and outpatient care facilities reported higher absenteeism among caregivers due to sickness or quarantine, such that 40 min on average of extra work per shift had to be compensated for by healthy colleagues as compared with before the pandemic [59], which resulted from the increased psychosocial burden that healthcare professionals were exposed to [60]. Accordingly, advice and information on awareness, such as newsletters and training courses, are equally important support measures, as Rohwer et al [61] demonstrated a link between perceived information sufficiency and pandemic-related worries and perceived stress. This also explains why the study participants in our survey mentioned responses such as "discussions with line managers" or "good teamwork" as support measures, although these are not measures in the true sense of the word.…”
Section: Support Measures In Outpatient Care In Relation To Covid-19mentioning
confidence: 96%
“…Furthermore, a study of German semi-residential and outpatient care facilities reported higher absenteeism among caregivers due to sickness or quarantine, such that 40 min on average of extra work per shift had to be compensated for by healthy colleagues as compared with before the pandemic [59], which resulted from the increased psychosocial burden that healthcare professionals were exposed to [60]. Accordingly, advice and information on awareness, such as newsletters and training courses, are equally important support measures, as Rohwer et al [61] demonstrated a link between perceived information sufficiency and pandemic-related worries and perceived stress. This also explains why the study participants in our survey mentioned responses such as "discussions with line managers" or "good teamwork" as support measures, although these are not measures in the true sense of the word.…”
Section: Support Measures In Outpatient Care In Relation To Covid-19mentioning
confidence: 96%
“…In this study, it was found that there was a significant relationship between the level of fear of COVID-19 and health literacy, and a high level of health literacy was associated with a low level of fear of COVID-19 [30]. In a study by Rohwer et al (2021) with caregivers during the COVID-19 process in Germany, it was reported that the perceived stress during the COVID-19 process and the anxiety associated with COVID-19 was associated with the level of health literacy [31]. This research shows that individuals' access to information, their level of understanding, and evaluation of information are effective on coronavirus phobia.…”
Section: Discussionmentioning
confidence: 61%
“…One of the main challenges of the strategy was to reach as many vulnerable people of different ages as possible, as has been done in similar studies and interventions [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ], but at the same time minimizing the technological gap that could leave someone behind, which is a common problem when trying to reach a vulnerable population using information technologies [ 9 , 26 , 27 ]. To do this, everyday technology tools already existing in homes, such as tablets and smartphones, were used, with no need for additional installation of complex programs.…”
Section: Discussionmentioning
confidence: 99%